BOOMING SENI LUKIS INDONESIA, SIAPA YANG DIUNTUNGKAN? - Satriana Didiek Isnanta (Pascasarjana Institut Seni Indonesia Surakarta, 2008)
In the development of fine art in Indonesia there was once an interesting phenom- enon, namely, â€œpainting boom.â€ Â It first happened in 1987, then in 1991-1992, in1999-2000, and the last in 2007. Â Painting was booming for the first time in coinci- dence Â with the economic crisis in 1997 and this phenomenon grew stronger.Â Â The economic crisis which was indicated by the collapse of private banks, the deprecia- tion of rupiah against dollar, and the stoppage of wheel of real sectors which led to unemployment in Â cities, caused capital flight and transfer of investment to other sectors, especially to artistic objects. Â Painting was suddenly believed as an object of investment which could Â give a big advantage in short time.Â Â Then a business community of painting emerged Â and most of the businesspersons were Chinese. And the paradigm changed from painting as a work of art which had philosophical- aesthetic value to a commodity which was Â subject to commerce law.Â Â In other words, painting had become a commodity and entered the global capitalist indus- try. Â And then the question is why painting could change into a special object which people were willing to collect and invest in.Â Â This writing is Â trying to answer the above question using an economic-politic approach and discuss who Â took part in making painting enjoy a boom and who was the most powerful and took an advan- tage.